DEVELOPING THE INDEPENDENT CHARACTER OF FOSTER CHILDREN THROUGH THE ORPHANAGE DORMITORY CURRICULUM - Maslahatun Nikmah; Abdullah Syukur (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
Curriculum is an important element in the implementation of education that functions as a guideline in the learning process to achieve educational goals effectively and systematically. In its implementation, the success of the curriculum is greatly influenced by curriculum ad-ministration and the role of teachers in shaping students’ learning experiences, including character education. One of the main characters emphasized in national education goals is independence. Independent character is important to be instilled from an early age because it affects children's ability to make decisions, take responsibility for themselves, solve prob-lems, and increase self-confidence and readiness to face social life. Especially for orphaned children, independence becomes an essential aspect in enabling them to face life’s challenges without dependence on others. This study aims to explore the character education curricu-lum in shaping the independent character of orphaned children. This research used a descrip-tive qualitative approach with data collection techniques including observation, in-depth in-terviews, and documentation. The results of this study indicate that the character education curriculum for students is implemented through various programs, such as psychological counseling, classroom learning activities, outdoor learning activities, independence develop-ment programs, and recreational excursions. This study recommends strengthening training for educators as well as improving the character evaluation system to support the sustaina-bility of character education programs in the dormitory.